Glucagon: Its evolving role in the management of hypoglycemia. Issue 7 (16th July 2021) - Isaacs, Diana; Clements, Jennifer; Turco, Neil; Hartman, Rachel
Abstract: More than 10% of the United States population has diabetes, characterized by hyperglycemia. Insulin and other agents used to treat diabetes predispose people to hypoglycemia, which can be life threatening. Glucagon is an emergency medication that can save lives by quickly raising glucose in people who are unconscious or unable to consume glucose due to severe hypoglycemia. Although glucagon has been commercially available since 1960, earlier formulations required reconstitution of a dry powder with diluent immediately prior to injection, due to lack of long‐term stability once reconstituted. Glucagon has been underutilized due to the lack of confidence or ability to administer in emergency situations. More recently, new formulations including a nasal powder glucagon and liquid‐stable glucagon have become available. This article discusses the evidence surrounding new glucagon formulations compared with the original glucagon emergency kit including ease of use, efficacy, and safety with a focus on important patient counseling points and relevant clinical information on hypoglycemia.